Cattle Hygiene Status and Its Relation with Subclinical Mastitis: A Study in Commercial Farms in Rampur, Nepal - Lamsal, Prativa (International Journal of Applied Sciences and Biotechnology, 2018)
Objective: The main objective of this study was to determine the hygiene status of cattle in commercial farms of Rampur and its association with subclinical mastitis. Study Design: Purposive study with cross sectional design. Methods and Methodology: Hygiene Scorecard devised by N.B Cook University of Wisconsin- Madison, USA was taken as reference to evaluate hygienic status of rear and hind parts of animal with score of 1 to 4, 1 for the cleanest and 4 for the dirtiest. For screening test of subclinical mastitis, California mastitis test with 211 cows with all their 4 quarters were examined from November 2015 till February 2016. Results: The overall prevalence rate was reported as 69% in cattle. Mean hygiene score of cow was 2.4 with udder, lower leg and flank being 2.80, 2.42 and 2.64 respectively. Mean CMT score of different quarters was found to be left front, left hind, right front, and right hind being 0.86, 0.83, 0.88, and 0.74 respectively. Hygiene score of cow of different parts and SCM presence percentage in all individual scores were calculated to make obvious relation that with increasing score from 1 to 4, SCM presence rate was increased making it clear that with compromised hygienic condition SCM presence was high. Conclusion: The study revealed that prevalence of Subclinical mastitis was high with increasing hygiene score of rear body parts that is with increasing unhygienic condition. Udder was competitively cleaner than rear and flank regions. Mastitis test (CMT) was done in a total of 211 cows with 844 quarters. Int. J. Appl. Sci. Biotechnol. Vol 6(3): 252-254